Intraductal papillary neoplasm of the bile duct. Issue 1 (2nd January 2019) - Le, Don K.; Agarwal, Atin
Abstract: Intraductal papillary neoplasm of the bile duct is characterized by intraductal papillary growth with fibrovascular cores that can grow anywhere along the biliary tree. Most cases have high-grade intraepithelial neoplasia or an associated invasive carcinoma. These tumors can spread superficially along the biliary tree and be multifocal, and preoperative biopsy cannot always reflect the maximum degree of atypia. Frozen section to assess the distal common bile duct margin is crucial to avoid the risk of recurrence. Theoretically, resection of the entire biliary tree by liver transplantation and pancreaticoduodenectomy is regarded as the only curative treatment.